Upaya perpustakaan dalam penguatan literasi di Perpustakaan Archivelago di Kementerian Kelautan dan Perikanan - Izzah, Rizka Nurul; Rachmawati, Tine Silvana; Rohman, Asep Saeful (Pustaka Karya : Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2023)
This paper investigates and analyze Archivelago Library efforts in literacy about marine and fisheries. This research focuses on program participated by the Bunayya Integrated Play Group, on November 16, 2022 in Jakarta. This research is qualitative type with descriptive study approach.  Data collection method by interview, documentation and literature study. The data is discussed with the theory of literacy, namely the theory of emergent literacy. Data analysis techniques in the form of data reduction, data presentation, and conclusions. The research subjects consisted of head librarians, librarians, and teachers from schools participating in this program. The results of this study showed that 39 childrens participated and were accompanied by 7 teachers. This program is carried out based on the planning concept in accordance with the Terms of Reference and the Minister of Maritime Affairs and Fisheries Regulation Number PER. 08/PERMEN-KP/2014 concerning Guidelines for Organizing Special Libraries. Based on the findings, the concept of this program focuses on forming mindsets, perspectives on oneself and the environment as a maritime nation. The various activities carried out include library tours, storytelling, watching movies, and coloring. The benefits of this program are not only felt by the participants, but also the Archivelago Library.